PROGRAM PARAKI GEN-Z: MENTORING MENYAPA MUDA DAN EDUKASI PENDEWASAAN USIA PERNIKAHAN DI DESA PEMAKUAN KABUPATEN BANJAR - Rahman, Fauzie; Wulandari, Anggun; Akbar, Alfito Dodi Forsatama; Putri, Aura Salsabila Yunizar; Rizki, Shofa Yulia; Wenda, Yonesi; Erlyani, Neka (Universitas Mataram, 2024)
The effort to improve the minimum marriage age in BKKBN’s program aims to raise the minimum age for marriage. South Kalimantan has the highest percentage of women aged 20-24 who were married before the age of 18, at 17.63%, exceeding the national average of 12.21%. Banjar Regency ranks second for underage marriages, with 95 cases in Pemakuan Village. Factors contributing to early marriages include a lack of knowledge among teenagers about its impact and parental influence. To increase the knowledge and awareness of teenagers participating in the Mentoring Menyapa Muda program regarding the maturation of marriage age and the consequences of underage marriage. The PARAKI Gen-Z program is a youth empowerment initiative carried out in stages, including program socialization, training, and evaluation. These are conducted through lectures, video screenings, and Q&A discussions. The program evaluation assesses participants’ knowledge before and after the activities, as well as their awareness. Prior to the program, 16 participants (80%) had little understanding of the BKKBN’s definition of early marriage and the benefits of delaying marriage until the ideal age. The average pre-test score was 72.08, which increased to 88.33 after the program, indicating a score improvement of 16.25%. Based on this analysis, it can be concluded that the program significantly increased the knowledge of 19 out of 20 participants. Participants gained not only additional knowledge about early marriage in general but also its health impacts. The participants demonstrated an increase in knowledge regarding marriage age maturity and showed awareness of the importance of preventing the adverse effects of underage marriage.